PELATIHAN ADVENTURE BASED COUNSELING UNTUK MENGATASI TIGA DOSA BESAR PENDIDIKAN - Rusmana, Nandang; Yudha, Eka Sakti; Kustiawati, Tati; Pasaribu, Berlima; Rohimah, Siti; Mudrikah, Syifa (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Educational institutions are faced with faced with the three major sins of bullying, sexual violence and intolerance that impact on students' psychological well-being. Therefore, a comprehensive comprehensive intervention is needed as an effort to facilitate students with traumatic experiences. This training aims to provide insight Guidance and Counseling (BK) teachers understand adventure-based counseling (ABC) as an effort to prevent and overcome trauma in individuals caused by bullying, sexual violence and intolerance. intolerance. The training program consisted of two phases: (1) an online workshop that introducing the concept of trauma in schools and the theoretical foundations of ABC, and (2) an offline training on practical ABC training offline using the APPLE Facilitation Model. Results The results of the training showed that, in general, trainees reported that the ease of in understanding the concept of types of traumata and ABC and applying it as part of the guidance and counseling of guidance and counseling services to address cases of bullying, sexual violence and intolerance